Comment les Satires de Juvénal sont arrivées au Mont Saint-Michel ? (enquête sur Paris, BnF, lat. 8070-I et sur son modèle) - Frédéric Duplessis (Tabularia)
The analysis of the content of the first codicological unit of the manuscript Paris, BnF, lat. 8070 allows us to study how Juvenal was read at Mont Saint-Michel shortly after the arrival of the Benedictines around the year 1000. The text of the Satires and their glosses show that the reception of the satirist at Mont Saint-Michel is influenced by the teaching of Remigius of Auxerre and that the model used by the Norman monks probably comes from a library in north-eastern France. The study of the school texts copied after the Satires in this manuscript (fol. 124-128) corroborates this link with schools of north-eastern France and we may assume the existence of a network of intellectual exchanges linking the Mont to the Reims region through Fleury or Corbie.